Polypenol Content Test, Antioxidant Activity Test and Sunblock Protection Test of Pinang Peels - Yulianis S.Farm, M.Farm, Apt; Armini Hadriyati; Mukhlis Sanuddin; Nofa Putriani; Indah Sagita Cahyani; Eka Fitriani (Jurnal Ipteks Terapan, 2020)
Areca nut skin contains phenolic compounds which have antioxidant and sunscreen activities. This study aims to determine the levels of polyphenols, antioxidant activity and sunscreen contained in the extract and fraction of areca nut (Areca catechu L.) skin. Testing levels of polyphenols using Folin-Ciocalteau reagents, testing of antioxidants using the DPPH method with a comparison of vitamin C, and on sunscreen testing using the UV-Vis spectrophotometry method by calculating the SPF value. The results of this study indicate that the fraction of n-Butanol has higher polyphenol levels compared to extracts and other fractions with polyphenol levels of 13.88974%. In antioxidant testing it was found that the n-hexane fraction had very strong antioxidant activity with an IC50 value of 40.848 mg / ml. In the sunscreen activity test, it was found that the highest SPF value was at a concentration of 300 ppm, in the thick ethanol extract, n-hexane fraction, ethyl acetate fraction, n-Butanol fraction, and residual water fraction. The highest sunscreen activity of SPF value is the ethyl acetate fraction that is 24.79. From the results of the study it can be concluded that the skin of betel nuts has antioxidant activity, sunscreen, and polyphenol levels.